Gender Differences in the Perceived Behavior of Narcissistic Leaders - Van Gerven, Emma J. G.; De Hoogh, Annebel H. B.; Den Hartog, Deanne N.; Belschak, Frank D. (Frontiers in Psychology, 2022)
Although narcissists often emerge as leaders, the relationship between leader narcissism and follower performance is ambiguous and often even found to be negative. For women, narcissism seems especially likely to lead to negative evaluations. Since narcissists have the tendency to be impulsive and change their minds on a whim, they may come across as inconsistent. We propose “inconsistent leader behavior” as a new mechanism in the relationship between leader narcissism and follower performance and argue that leader gender plays an important role in whether narcissistic leaders are perceived as inconsistent. Specifically, we expect leader narcissism to have a negative relationship with follower performance through perceived inconsistent leader behavior, especially for female leaders. Thus, we examine leader gender as a personal factor moderating the relationship between narcissism and perceived inconsistent behavior. Also, as perceived inconsistency is likely less problematic when a good relationship exists, we examine leader–member exchange (LMX) as a contextual condition moderating the relationship between leader behavior and follower performance. We test our moderated mediation model in a multi-source study with 165 unique leader–follower dyads. As expected, leader narcissism was positively related to perceived inconsistent leader behavior, and this relationship was stronger for female leaders. Inconsistent leader behavior was negatively related to follower performance, but only when LMX was low. Our research highlights that perceived behavioral inconsistency can be problematic and—for female leaders—provides an explanation of the negative relation of leader narcissism with follower performance and of the inconsistencies in evaluations of narcissistic leaders’ effectiveness.